Revealing Story Messages Through Symbols in William Golding’s Lord of the Flies - Maharani, Vincentia Deswita Mayke; Prabandari, Carla Sih; Herawati, Henny (Universitas Negeri Makassar, 2025)
Abstract. Literary works, such as novels, are a means used to express human experiences, thoughts, and feelings. William Golding’s novel Lord of the Flies is one of the works frequently discussed for its use of symbolism in conveying meanings. Understanding symbolism in literature can enhance readers’ ability to interpret the deeper messages embedded in a story. Often, these messages are not explicitly stated, but must be uncovered as the story unfolds. This study aims to answer two research questions: (1) “What symbols are found in the novel Lord of the Flies by William Golding?” and (2) “What do they symbolize?” This qualitative study employs a formalist critical approach, focusing on the form and structure of the story itself, without reference to external aspects. Close textual analysis method is used, supported by Stanton’s (1965) theory of symbols for classification and Nurgiyantoro’s (2015) theory of meaning to interpret implicit messages. The study identifies nineteen symbols in the novel, namely palm trees, the conch shell, Piggy’s glasses, the fire, the beast, the mask, Lord of the Flies, Jack’s knife, the scar, Ralph, Jack, the littluns, Roger, Piggy’s death, the breaking of the conch, the spear, the pig hunting, the darkness, and the daylight. These symbols are associated with five interrelated meanings, namely (1) outward looks can be deceiving; (2) the evil or dark side of human nature; (3) human behaviors, as manifestation of either the good or the dark side of human nature, such as self-control and savagery; (4) the tension between a stable community and the collapse of civilization; and (5) hope for a better life. The findings contribute to the global literary studies that themes of human nature and social conflict can be intricately conveyed using symbolism. This underlines the significance of Lord of the Flies as an important resource in literature-based English language learning, as well as in fostering critical thinking. Keywords: Lord of the Flies, novel, symbols, interpretation